The Effect of Market Orientation and Entrepreneurial Orientation on the Marketing Performance of Msmes in Deket District - Bella Fernanda; Mohammad Yaskun; Imam Syairozi (Sean Institute, 2024)
This study aims to analyze the influence of market orientation and entrepreneurial orientation on the marketing performance of MSMEs in Deket District. The study used a descriptive quantitative approach with a population of 4,581 MSME actors. The research sample of 98 respondents was determined using the Slovin formula with an error rate of 10% and a simple random sampling technique. Primary data is collected through a Likert scale questionnaire, while secondary data is obtained through relevant documentation. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and determination coefficient with the help of SPSS. The results of the study show that all indicators are valid and reliable. The regression equation obtained is Y = 3.701 + 0.297X1 + 0.399X2. Partially, market orientation has a positive and significant effect on marketing performance with a t-value of 2.730 and a significance of 0.008. Entrepreneurial orientation also had a positive and significant effect with a t-value of 3.408 and a significance of 0.001. Simultaneously, market orientation and entrepreneurial orientation had a significant effect on marketing performance with an F value of 13.289 and a significance of 0.000. The R-Square value of 0.219 indicates that 21.9% of the variation in marketing performance can be explained by market orientation and entrepreneurial orientation, while the rest is influenced by other factors.